Layer-by-Layer Fabrication of Hydrogel Microsystems for Controlled Drug Delivery From Untethered Microrobots - Bernasconi, Roberto; Pizzetti, Fabio; Rossetti, Arianna; Butler, Brendan; Levi, Marinella; Pané, Salvador; Rossi, Filippo; Magagnin, Luca (Frontiers in Bioengineering and Biotechnology, 2021)
Targeted drug delivery from untethered microrobots is a topic of major interest in current biomedical research. The possibility to load smart materials able to administer active principles on remotely in-vivo guidable microdevices constitutes one of the most attractive opportunities to overcome the drawbacks of classical untargeted delivery methodologies. Hydrogels, in particular, are ideal candidates as drug carrying materials due to their biocompatibility, low cost and ease of manufacturing. On the other hand, these polymers suffer from poor control over release rate and overall released amount. Starting from these premises, the present paper demonstrates the possibility to tune the release of hydrogels applied on magnetically steerable microrobots by fabricating microsystems via layer-by-layer self-assembly. By doing this, diffusion of chemicals from the hydrogel layers to the external environment can be optimized and the phenomenon of burst release strongly limited. The microrobotic platforms employed to transport the hydrogel active material are fabricated employing 3D printing in combination with wet metallization and present a gold layer on their surface to enhance biocompatibility. The manoeuvrability of microdevices coated with both thin and thick multilayers is investigated, individuating optimized parameters for efficient actuation.